Structural Analysis of Parking Barrier Made of Polymeric Resin Using Ansys Software - Zoanri Purba; Maraghi Muttaqin; Bustami Syam; Ade Irwan; Fakhrur Rozy (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
A barrier gate is a stopping tool that has a security function in a place such as an office or agency entrance. This study aims to examine the response of the beam structure of the polymer composite material due to the support test. The parking portal material in this research is BQTN 157 EX resin, MEKPO catalyst, fiberglass. There are two parking portal compositions with impact test heights of 2 m and 4 m which will be simulated with ansys software. Overall, from two types of compositions, namely polymeric reinforced fiberglass composition A and composition B by looking at the results of the equivalent stress distribution (von-mises), it is concluded that polymeric reinforced fiberglass composition A has a higher maximum stress than polymeric reinforced fiberglass composition. reinforced with fiberglass composition B. From the comparison between simulation and experiment, it is known that the composition of rod A has a different damage position between simulation and experiment. While the composition of rod B in the simulation of the same damage position occurs, namely in the crossbar area connected to the transmission shaft and the experimental also has a damage position in the crossbar area connected to the transmission shaft.